ANALISIS KEPUASAN MAHASISWA FKIP UNIVERSITAS TANJUNGPURA TERHADAP IMPLEMENTASI KEBIJAKAN PROGRAM KAMPUS MENGAJAR ANGKATAN 2 - Sari, Iga Fiolita; Zakso, Amrazi; Purnama, Shilmy; Mashudi, Mashudi; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to get a clear picture of the level of satisfaction of students at the University's Faculty of Teacher Training and Science (FKIP) regarding the implementation of the 2nd generation campus teaching policy program. In connection with the research objectives above, the method used in this research is a quantitative research method with a descriptive approach, where the subjects or samples in this research are 113 FKIP Tanjungpura University students who have participated in the 2nd generation campus teaching program. Meanwhile, the data collection technique used is a questionnaire with a rating assessment scale. The students sampled as part of the research will answer several statements in the research related to the implementation of the 2nd generation campus teaching program by choosing an answer rating scale of 1 - 4 (very dissatisfied - very satisfied). The questionnaire will be distributed via Google Form media. The results of the research show that the level of satisfaction of Tanjungpura University FKIP students is relatively high with the class 2 campus teaching program, namely reaching 77.9% with a percentage of student dissatisfaction of only 22.1%.